Experimental study on the effect of long-term ethanol intake on the rat parotid glands - MATSUO, Masaatsu (Japanese Journal of Oral and Maxillofacial Surgery, 1989)
To elucidate the effect of long-term intake of ethanol on the parotid gland, observations of parotid glands from male Wistar Strain rats given 20% ethanol ad lib. instead of water were performed, using light and electron microscopy. Results were as follows:(1) Under the light microscope, 3 rats (11%) demonstrated several lesions involving complete lobular units, and (2) under the electron microscope, the earliest and most consistent changes after ethanol intake were the irregular formation of microvilli and interdigitation between parenchymal cells. These were accompanied by widening of the intercellular spaces and disappearance of the basal infolding structure with severe mitochondrial alteration in striated duct cells. Tortous proliferation of intercalated duct cells was observed after 4 months of ethanol intake. These results suggest that the intake of ethanol leads to injury of the inter-parenchymal cell membranes and to the basal membranes of striated duct cells. Repeated degeneration and regeneration of duct cells during the repair process results in deformation of ductal structure at the level of the intercalated ducts, followed by the degeneration and subsequent atrophy of the acini.